1993
DOI: 10.1016/0165-1838(93)90377-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peri-arterial hepatic denervation on the glycemic response to exercise in rats

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…It seems from most studies that the counterregulatory reaction on hypoglycemia (insulin‐induced), exercise (swimming, running), and food deprivation is normal (Lindfeldt et al, 1993; Moore et al, 1993; Latour et al, 1995; Trabelsi et al, 1995; Wiersma et al, 1995; Jackson et al, 2000). These data suggest that afferent signaling from the liver is not required for the normal counterregulating response.…”
Section: Effect Of Hepatic Denervation In Experimental Animal Modelsmentioning
confidence: 99%
“…It seems from most studies that the counterregulatory reaction on hypoglycemia (insulin‐induced), exercise (swimming, running), and food deprivation is normal (Lindfeldt et al, 1993; Moore et al, 1993; Latour et al, 1995; Trabelsi et al, 1995; Wiersma et al, 1995; Jackson et al, 2000). These data suggest that afferent signaling from the liver is not required for the normal counterregulating response.…”
Section: Effect Of Hepatic Denervation In Experimental Animal Modelsmentioning
confidence: 99%
“…Similarly, in swimming rats, the exercise‐induced increase in hepatic glucose formation was attributed primarily to an increase in glucagon secretion. Circulating adrenaline and hepatic nerves became important only if glucagon secretion was suppressed (Lindfeldt et al, 1993; Van Dijk et al, 1994). Dog and rat liver parenchyma is scarcely innervated.…”
Section: Sympathetic Control Of Hepatic Glucose Outputmentioning
confidence: 99%
“…hepatic denervation and adrenodemedullation studies in animals that have suggested the greater importance of Epi than NE in stimulating R a (23,44). One study of Epi infusion during exercise was performed on celiac ganglion-blocked and islet cell-clamped human subjects exercising at 74% V O 2 max .…”
mentioning
confidence: 99%